Ideal Photothermal Materials Based on Ge Subwavelength Structure - Jingjun Wu; Kaixuan Wang; Cong Wei; Jun Ma; Hongbo Xu; Wanguo Zheng; Rihong Zhu (Molecules)
Photothermal materials often prioritize solar absorption while neglecting thermal radiation losses, which diminishes thermal radiation conversion efficiency. This study addresses this gap by introducing a germanium (Ge) subwavelength structure (SWS) designed to optimize both solar absorption and infrared emissivity. Using a self-masked reactive ion etching (RIE) technique, we achieved a peak absorption of 98.8% within the 300 nm to 1800 nm range, with an infrared emissivity as low as 0.32. Under solar illumination of 1000 W/m2, the structure’s temperature increased by 50 °C, generating a heating power of 800 W/m2. Additionally, it demonstrated good mechanical and thermal stability at high temperatures and possessed a hydrophobic angle of 132°, ensuring effective self-cleaning. These characteristics make the Ge SWS suitable for application in solar panels, displays, sensors, and other optoelectronic devices.